Molecular basis of the microtubule-regulating activity of microtubule crosslinking factor 1. - Mohammad Abdul Kader; Tomoko Satake; Masatoshi Yoshida; Ikuko Hayashi; Atsushi Suzuki (PLoS ONE)
The variety of microtubule arrays observed across different cell types should require a diverse group of proteins that control microtubule organization. Nevertheless, mainly because of the intrinsic propensity of microtubules to easily form bundles upon stabilization, only a small number of microtubule crosslinking proteins have been identified, especially in postmitotic cells. Among them is microtubule crosslinking factor 1 (MTCL1) that not only interconnects microtubules via its N-terminal microtubule-binding domain (N-MTBD), but also stabilizes microtubules via its C-terminal microtubule-binding domain (C-MTBD). Here, we comprehensively analyzed the assembly structure of MTCL1 to elucidate the molecular basis of this dual activity in microtubule regulation. Our results indicate that MTCL1 forms a parallel dimer not only through multiple homo-interactions of the central coiled-coil motifs, but also the most C-terminal non-coiled-coil region immediately downstream of the C-MTBD. Among these homo-interaction regions, the first coiled-coil motif adjacent to N-MTBD is sufficient for the MTCL1 function to crosslink microtubules without affecting the dynamic property, and disruption of this motif drastically transformed MTCL1-induced microtubule assembly from tight to network-like bundles. Notably, suppression of the homo-interaction of this motif inhibited the endogenous MTCL1 function to stabilize Golgi-associated microtubules that are essential for Golgi-ribbon formation. Because the microtubule-stabilizing activity of MTCL1 is completely attributed to C-MTBD, the present study suggests possible interplay between N-MTBD and C-MTBD, in which normal crosslinking and accumulation of microtubules by N-MTBD is essential for microtubule stabilization by C-MTBD.